Nutritional composition of commonly consumed composite dishes from rural villages in Empangeni, KwaZulu‐Natal, South Africa. Issue 3 (6th December 2012) - Spearing, K.; Kolahdooz, F.; Lukasewich, M.; Mathe, N.; Khamis, T.; Sharma, S.
Abstract Background Accurate nutrient composition data for composite dishes unique to a population is essential for the development of a nutrient database and the calculation of dietary intake. The present study aimed to provide the nutritional composition of composite dishes frequently consumed in rural KwaZulu‐Natal, South Africa. Methods Commonly consumed composite dishes were identified using 24‐h recalls collected from 79 randomly selected community members. Multiple recipes were collected for each reported dish. The mean nutritional composition of each dish was calculated per 100 g using the nutribase clinical nutrition manager (Cybersoft Inc., Phoenix, AZ, USA). Results A total of 79 recipes were collected for 16 commonly consumed dishes (seven meat‐based, five starch‐based and four legume/vegetable‐based). 'Fried chicken' contained the most energy [1469 kJ (351 kcal)], protein (29.7 g), fat (23.7 g), cholesterol (123 mg) and niacin (8.4 mg). 'Fried beef' contained the most potassium (495 mg) and zinc (6.4 mg), whereas 'fish stew' had the most vitamin D (4.2 μg) and calcium (215 mg). 'Fried cabbage' and 'fried spinach' contained the largest percent energies from fat, at 79% and 76%, respectively. A traditional sweet bread, 'jeqe', made with fortified flour contributed significantly to iron (4.6 mg), niacin (4.5 μg) and folate (129 μg). The sodium content of dishes ranged from 88 to 679 mg per 100 g. Conclusions The nutritional composition data for commonly consumed dishes in rural KwaZulu‐Natal is presented. Although the dishes are good sources of protein, vitamins and minerals, they also contain substantial amounts of fat. This culturally appropriate information will enable the calculation of dietary intake and can be used to encourage the consumption of recipes rich in key nutrients.